Firearms Trafficking in the Sahel - United Nations Office on Drugs; Crime (United Nations, 2023)
Firearms Trafficking in the Sahel is part of a series of transnational organized crime threat assessment reports on the Sahel. The report explores firearms trafficking in the Sahel by looking at the nature of the market, trafficking flows, the main actors involved, as well as the enablers and impact of this form of trafficking on the region. While there is evidence of long-range firearms trafficking to the Sahel, including by air from France and from Turkey via Nigeria, it appears that the vast majority of firearms trafficked in the region are procured within Africa. Since 2019, Libya has become a source of supply for newly manufactured weapons. Apparently, newly produced AK-pattern assault rifles, sourced from Libya, are available on the black market in Gao, Timbuktu and Ménaka regions of northern Mali.